Pengaruh Punishmen terhadap Efek Jera Santriwati di Pondok Pesantren Al-Hamidiyah Sawangan-Depok - Annisa Dwi Fitrianingrum; Faza Karimatul Akhlak (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This research is a type of quantitative research conducted at the Al-Hamidiyah Islamic Boarding School in Sawangan Depok, starting from February to July 2019. The population in this study was all female students of class X Al-Hamidiyah Islamic Boarding School in Sawangan Depok, with a sample of 42 female students using the Simple Cluster Random Sampling technique. Data collection using a questionnaire. Instrument analyst technique uses validity and reliability tests. Hypothesis testing using product moment. The results showed that: 1) There is an influence on the implementation of punishment on the deterrent effect of students who violate the rules of the Islamic Boarding School Al-Hamidiyah Sawangan Depok. The alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected because the result of